Online-Processing of Grammatical Gender in Noun-Phrase Decoding: An Eye-Tracking Study With Monolingual German 3rd and 4th Graders - Cholewa, Jürgen; Neitzel, Isabel; Bürsgens, Annika; Günther, Thomas (Frontiers in Psychology, 2019)
Like many other languages, German employs a linguistic category called “grammatical gender”. In gender-marking languages each noun is assigned to a particular gender-class (in German: masculine, feminine or neuter) and other words in a sentence which are grammatically controlled by the noun are marked by particular morphemes according to the noun’s gender feature – so called gender agreement. Within psycholinguistic theories of language comprehension, it is often assumed that gender agreement might help to predict the continuation of a sentence on grammatical grounds and to reduce the lexical search space for the next words emerging within the speech signal. Thus, gender agreement relations may provide a means to make the comprehension process more effective and targeted. The aim of the current study was to assess whether monolingual German 3rd and 4th grade primary school children make use of gender agreement in online auditory comprehension and whether different gender cues interact with each other and with semantic information. A language-picture matching task was conducted in which 32 children looked at two pictures while listening to a noun phrase. Due to features of the German gender system, the target picture corresponding with the noun phrase could be predicted shortly after stimulus onset on account of gender agreement relations. The predictive impact of grammatical gender agreement on noun-phrase decoding was investigated by measuring the time course of eye-movements onto the target and distractor pictures. The results confirm and extend previous findings that gender plays a role in predictive online comprehension of gender-marking languages like German, and that even primary school children are able to make use of this grammatical device.